A Comparative Pharmaco-Clinical Study of (Ficus Racemosa Linn.) and Indravaruni Phala Churna (Citrullus Colocynthis Schrad.) in the Management of Madhumeha (Type-2, Diabetes Mellitus) (AYUSHDHARA, 2025)
One of the contemporary global health issues is diabetes mellitus. Because of their Pramehaghna (anti-diabetic) qualities and the numerous clinical trials in diabetes, Indravaruni Phala Churna are used to treat Madhumeha (diabetes mellitus). In order to compare the effects of Indravaruni Phala Churna, which are both manufactured in capsule form, on type 2 diabetes, the current study was conducted. Materials and methods: 60 patients with type 2 diabetes were treated with lukewarm water (1gm) and Indravaruni Phala Churna with lukewarm water (500mg) twice daily before meals for 60 days in this prospective, randomized, single-blind clinical experiment. Assessments were made of the alterations in hemoglobin, blood sugar, HbA1c, lipid profile, hepatic, renal, and clinical complaints. Results: and Indravaruni Phala Churna experienced a significant decrease in fasting blood glucose levels and a significant decrease in postprandial blood glucose levels following a 60-day treatment regimen. During the trial period, no adverse effects were reported. Conclusion: Compared to Ama Udumbara Phala Churna, Indravaruni Phala Churna is more successful, enhancing patients' quality of life while also providing significant glycemic control and having no negative side effects.